NOGAPS-ALPHA Simulations of the 2002 Antarctic Stratospheric Major Warming - Allen, D. R.; Eckermann, S. D.; McCormack, J. P.; Coy, L.; Manney, G. L.; Hogan, T. F.; Kim, Y.-J. (2005)
A new high-altitude (~0-85 km) version of the Navy Operational Global Atmospheric Prediction System (NOGAPS) global spectral forecast model has been developed as a joint effort of NRL's Space Science, Remote Sensing, and Marine Meteorology Divisions. This NOGAPS-Advanced Level Physics and High Altitude (NOGAPS-ALPHA) model is formulated with a higher top level than the operational NOGAPS model and with a new hybrid vertical coordinate that transitions from terrain-following in the lower atmosphere to constant pressure levels in the stratosphere. New physics packages were added to adequately simulate the higher altitudes. These include a new radiation scheme, new gravity wave drag parameterizations, and new prognostic ozone capability. In addition, a new initialization procedure was developed for the upper atmosphere, and capability for transporting multiple trace species was added. To assess the impact of these changes on model forecast skill, we examine NOGAPS-ALPHA hindcasts of the Southern Hemisphere (SH) during September to October 2002; this was an unusual period when the first ever Antarctic major stratospheric sudden warming was observed. Published in the 2005 NRL Review: Atmospheric Science and Technology, p109-112, Dec 2005; NRL/PU/3404--05-481. Expanded version with similar title published in Monthly Weather Review, v134, p498-518, Feb 2006.